Grapevine red blotch-associated virus is Present in Free-Living Vitis spp. Proximal to Cultivated Grapevines - Perry, Keith L; McLane, Heather; Hyder, Muhammad Z; Dangl, Gerald S; Thompson, Jeremy R; Fuchs, Marc F (Phytopathology, 2016)
Red blotch is an emerging disease of grapevine associated with grapevine red blotch-associated virus (GRBaV). The virus spreads with infected planting stocks but no vector of epidemiological significance has been conclusively identified. A vineyard block of red-blotch-affected Vitis vinifera 'Cabernet franc' clone 214 was observed in California, with a clustering of infected, symptomatic vines focused along one edge of the field proximal to a riparian habitat with free-living Vitis spp. No genetic heterogeneity was observed in a 587-nucleotide region of the GRBaV genome in a population of 44 Cabernet franc clone 214 isolates. By contrast, genetic differences were observed in isolates from other cultivars and clones growing in adjacent blocks. GRBaV was confirmed infecting four free-living vines, two of which were shown to be V. californica × V. vinifera hybrids. The genomes of three free-living GRBaV vine isolates and seven from V. vinifera cultivars were compared; free-living vine isolates were shown to be more similar to each other and a 'Merlot' isolate than to the other cultivated vine isolates. The finding that GRBaV is present in free-living Vitis spp. indicates the virus can be spread by natural (nonhuman-mediated) means, and we hypothesize that in-field spread of GRBaV is occurring.